2018
DOI: 10.1016/j.learninstruc.2017.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening networks: A social network intervention among higher education teachers

Abstract: a b s t r a c tTeachers' opportunities to learn at the workplace are shaped by the relationships in which they discuss their instructional practice, what we call teaching networks. This study examined the extent to which such teaching networks could be strengthened during a professional development (PD) program. An intervention was designed to evaluate whether the development of teaching networks was affected in terms of network composition and access to teaching content. Longitudinal ego-network data of Belgi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
58
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 60 publications
(86 reference statements)
7
58
0
Order By: Relevance
“…For example, Akkerman and Bruining (2016) found in a five-year analysis of boundary crossing in a professional development school partnership that key individuals (i.e., brokers) provided essential linkages and opportunities for boundary crossing between different groups and institutions. Similarly, in a two-year longitudinal study amongst 38 academics, Van Waes, De Maeyer, Moolenaar, Van Petegem, and Van den Bossche (2017) found that professionals actively develop formal and informal relations beyond their own group and discipline.…”
Section: Boundary Crossing and Inter-group Learningmentioning
confidence: 95%
“…For example, Akkerman and Bruining (2016) found in a five-year analysis of boundary crossing in a professional development school partnership that key individuals (i.e., brokers) provided essential linkages and opportunities for boundary crossing between different groups and institutions. Similarly, in a two-year longitudinal study amongst 38 academics, Van Waes, De Maeyer, Moolenaar, Van Petegem, and Van den Bossche (2017) found that professionals actively develop formal and informal relations beyond their own group and discipline.…”
Section: Boundary Crossing and Inter-group Learningmentioning
confidence: 95%
“…Another experiment showed that network diagnostics helped in targeting only adolescents without friends who used substances for an intervention to reduce substance use (Valente et al 2007), because the intervention was only effective for this group. Last, interventions were successful in creating new social advice and discussion networks for children (Gesell et al 2013), and in expanding and strengthening professional networks of university teachers (Van Waes et al 2018).…”
Section: Network Diagnostics To Recognize and Reduce Victimizationmentioning
confidence: 99%
“…We have benefited from the reciprocal nature of the group in many ways. Our international makeup has helped to familiarize us with SoTL practices other than our own and has enabled us to draw from a deep well of practical and theoretical knowledge we would otherwise not have (Blair, 2013;Van Waes et al, 2018). It has enabled us to learn about the differences and similarities in our approaches to SoTL, and has connected us as we learn from and with one another (Felten, 2013).…”
Section: Final Notes: Implications and Conclusionmentioning
confidence: 99%
“…There are a number of other applications for this highly adaptable and inclusive format (Van Waes et al, 2018). It can be used for professional support, as many of us who have limited support for SoTL in our areas have experienced.…”
Section: Final Notes: Implications and Conclusionmentioning
confidence: 99%